Effects of annealing time on the structure and optical properties of ZnAl2O4/ZnO prepared via citrate sol-gel process. (March 2018) - Motloung, Setumo Victor; Kumari, Pushpa; Koao, Lehlohonolo Fortune; Motaung, Tshwafo Elias; Hlatshwayo, Thulani Thokozani; Mochane, Mokgaotsa Jonas
Abstract: ZnAl2 O4 nano-powders have been successfully prepared via citrate sol-gel technique. All powder samples were annealed at 600 °C for 1, 2, and 3 h. Thermogravimetric analysis (TGA) confirmed that the minimum annealing temperature of crystallization is ∼400 °C. Fourier Transform Infrared (FTIR) results showed a series of absorption peaks in the range of 810–4000 cm −1 . The X-ray diffraction (XRD), scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HR-TEM) results showed that the prepared nano-crystals consists of the mixture of both cubic (ZnAl2 O4 ) and hexagonal (ZnO) structures. Ultra violet visible (UV–vis) spectroscopy revealed that the annealing time (AT) influences the band gap of the prepared phosphor materials. When the samples were excited at 275 nm, two emission peaks at 428 nm (violet) and 561 nm (green-yellow) were observed and they are attributed to the defects levels within the ZnO and ZnAl2 O4 band gaps. The Commission Internationale de l'Elcairage (CIE) colour coordinates confirmed that all the prepared samples exhibit the violet emission and varying the AT does not influence the emission colour.